Influence of using synbiotics by various routes on Mandarah male chicks: intestinal bacterial counts, gut morphology and histological status - Islam M. Youssef; Ahmed I. Elsherbeni; Areej A. Almuraee; Nada M. Nass; Eman A. Beyari; Naheda M. Alshammarii; Ahmed M. Abdel-Ghany; El- Sayed G. Ahmed; Samia Nasr; Khaled M. Youssef; Heba M. Salem; Mohamed E. Abd El-Hack; et al. (Poultry Science, 2024)
ABSTRACT: This experiment investigated the influence of different synbiotic processing methods on the intestinal bacterial count, morphology and histological status of developed male Mandarah chicks. Two hundred and ten male Mandarah line chicks aged 1 d were randomized to receive one of 7 chicks. The method and dose for 1-time synbiotics administration to the day-old chicks were as follows: G1: chicks on basal diet received no treatment (control); G2: 0.25 mL synbiotics sprayed; G3: 0.50 mL synbiotics sprayed; G4: 0.25 mL of synbiotics are added to drinking water; G5: 0.50 mL of synbiotics are added to drinking water; G6: 0.25 mL of synbiotics dripped into the mouth; and G7: 0.50 mL of synbiotics dripped into mouth drops. Lactic acid bacteria (LAB) were significantly increased (P<0.0001) compared to the control group and other treated groups and had the maximum values after the use of synbiotics via drinking water (0.25 or 0.50 mL). Furthermore, when comparing the treated birds (G4, G5) with the control birds, the Escherichia coli concentration in the drinking water containing synbiotics was significantly lower. In addition, treated chickens at (G7) showed a higher duodenum, ileum villus height (VH), and VH. - Ileum crypt depth (CD) ratio compared to other groups. In addition, birds treated with 0.50 mL of synbiotics in drinking water (G5) performed better in duodenum, ileum, CD and VH. - CD ratio than the other groups. Meanwhile, intestinal tract length and visceral pH did not differ significantly between groups. It can be concluded that the use of 0.25 mL of synbiotics in drinking water can improve the overall health of birds.